Comparison of preemptive effect of intravenous ketorolac versus meperidine on postoperative shivering and pain in patients undergoing cesarean section under spinal anesthesia: A prospective, randomized, double-blind study - Marzieh Beigom Khezri; Maryam Al-sadat Mosallaei; Mahdi Ebtehaj; Navid Mohammadi (Babol University of Medical Sciences, 2018)
Background: Pain and shivering are two unpleasant problems in postoperative period. Various techniques are used to alleviate the postoperative shivering and pain.  We compared the preemptive prescription of a single dose of intravenous meperidine and ketorolac on postoperative pain and shivering in patients undergoing cesarean section with spinal anesthesia. Methods: One hundred and fifty patients who were scheduled for elective cesarean section under spinal anesthesia were randomly allocated to one of three study groups to receive either intravenous ketorolac (group K), meperidine (group M) or normal saline (group P). Time to first analgesic request, analgesic requirement in the first 24 hours after surgery, body tympanic temperature, hemodynamic variables and incidence of shivering were assessed as outcome variables. Results: There was no significant difference between meperidine and ketorolac groups in terms of prevalence of shivering, although both groups were different from the placebo group (p<0.04). The mean time to first analgesic request was longer in group k (3.8±1.4) and groups M (3.3±1.2) than in group P (2.1±0.8) hours (p<0.001). Conclusions: The preemptive prescription of a single dose of intravenous meperidine and ketorolac can provide a satisfying analgesia immediately after surgery and decrease shivering prevalence without any serious side effects.